2009
DOI: 10.1007/s10290-009-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher productivity in importing German manufacturing firms: self-selection, learning from importing, or both?

Abstract: This paper uses a newly available comprehensive panel data set for manufacturing enterprises from 2001 to 2005 to document the first empirical results on the relationship between imports and productivity for Germany, a leading actor on the world market for goods. Furthermore, for the first time the direction of causality in this relationship is investigated systematically by testing for self-selection of more productive firms into importing, and for productivity-enhancing effects of imports ('learning-by-impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(101 citation statements)
references
References 26 publications
11
86
3
1
Order By: Relevance
“…The first is to examine the selection effect in importing or the selection effects in exporting and importing simultaneously. Muuls and Pisu (2009), Castellani et al (2010) and Vogel and Wagner (2010) found that firms involved in both importing and exporting are better performers than those involved only in exporting or importing. However, no conclusion has been reached as to which requires higher productivity in exporting or importing.…”
Section: Evidence Of Globalization and Firm Productivitymentioning
confidence: 97%
See 1 more Smart Citation
“…The first is to examine the selection effect in importing or the selection effects in exporting and importing simultaneously. Muuls and Pisu (2009), Castellani et al (2010) and Vogel and Wagner (2010) found that firms involved in both importing and exporting are better performers than those involved only in exporting or importing. However, no conclusion has been reached as to which requires higher productivity in exporting or importing.…”
Section: Evidence Of Globalization and Firm Productivitymentioning
confidence: 97%
“…However, no conclusion has been reached as to which requires higher productivity in exporting or importing. Muuls and Pisu (2009) and Castellani et al (2010) find better performance in importers than exporters, whereas the opposite result was found in Vogel and Wagner (2010). The other direction is to investigate the relationship between the selection effect and a trading partner country.…”
Section: Evidence Of Globalization and Firm Productivitymentioning
confidence: 99%
“…and importing) increased turnover growth by 7% on average. Vogel and Wagner (2010) and Haller (2012) similarly found a trade premium for two-way traders for manufacturing firms in Germany and Ireland respectively. Importing provides SMEs with access to better quality intermediate goods, while exporting offers access to global markets.…”
Section: Firm Strategymentioning
confidence: 99%
“…Exports also provide access to global markets-this is particularly important for SME performance in small open economies such as Ireland. Importing may offer SMEs access to higher quality and a wider range of inputs at lower cost (Vogel and Wagner 2010). This may lead to better product quality and higher productivity.…”
Section: Internal Determinants Of Firm Growthmentioning
confidence: 99%
“…Conversely, results are slightly different when the analysis on post‐entry effects is carried out for firms in large economies. Vogel and Wagner () find evidence that efficiency affects positively self‐selection in import activity, whereas they do not find evidence of learning by importing. Similarly, Castellani et al .…”
Section: Background Literaturementioning
confidence: 99%